Loneliness: Self-Discrepancy and Sociological Variables - Moore, J. A. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study attempted to verify various viewpoints about loneliness. In a sample of first-year college women, loneliness was related to a discrepancy between perceived and reflected self, and father's level of income.There was no support for loneliness being related to discrepancies between perceived and ideal self, ideal and reflected self, number of changes in residence and mother's level of education.